P1585FACTORS ASSOCIATED WITH PSOAS MUSCLE INDEX IN PATIENTS WITH MAINTENANCE DIALYSIS: FOR EARLY DETECTION OF SARCOPENIA. (6th June 2020) - Mori, Yoshiko; Sawada, Tomohiro; Sunohara, Keisuke; Owaki, Akiko; Nagaya, Hiroshi; Inaba, Shinichiro
Abstract: Background and Aims: Frailty was known to be associated with higher rates of hospitalization and mortality in dialysis patients, and sarcopenia was documented as the biological substrate of physical frailty. Therefore, early-detecting sarcopenia in dialysis patients is important for improving prognosis. The aim of our study was to investigate the factors associated with low skeletal muscle mass in dialysis patients. Method: We recruited 134 Japanese patients (male 94, female 40; 117 maintenance hemodialysis, 11 chronic peritoneal dialysis and 6 both HD and PD) who underwent maintenance dialysis at our hospital during April 2019. Computed tomography (CT) imaging at the third lumbar vertebrae level was used to measure the psoas muscle mass index (PMI, psoas muscle area (cm2)/ height (m2) ), and low skeletal muscle mass was defined as under 6.36 cm2/m2 in male and 3.92 cm2/m2 in female. Results: The prevalence of low skeletal muscle mass was 19.4% in dialysis patients (26/134). The median values of PMI were 5.13 and 7.42 cm2/m2 in low skeletal muscle mass group and normal group, respectively. Univariate analysis identified variables associated with low skeletal muscle mass as follows: gender, age, body mass index, waist circumference, presence of coronary artery disease, total protein, albumin, asparate aminotransferase, γ-glutamyl transpeptidase, phosphorus, visceral fat area and subcutaneous fat area. Multiple logistic regression analysis using above significant factors identified independent variables associated with low skeletal muscle mass as follows: gender (male) (odds ratio [OR], 12.91; 95%confidence interval [CI], 2.50-66.57; p<0.01), age (per 1 year aging) (OR, 1.07; 95%CI, 1.00-1.14; p<0.05), waist circumference (per 1cm decrease) (OR, 1.11; 95%CI, 1.04-1.19; p<0.01), and albumin (per 1g/dL decrease) (OR, 5.55; 95%CI, 1.49-19.9; p<0.05). In sub-analysis targeting only male patients, age (per 1 year aging) (OR, 1.09; 95%CI, 1.01-1.17; p<0.05), waist circumference (per 1cm decrease) (OR, 1.13; 95%CI, 1.05-1.21; p<0.01) and albumin (per 1g/dL decrease) (OR, 5.88; 95%CI, 1.39-25.9; p<0.05) were independent factors associated with low skeletal muscle mass. Conclusion: In patients who underwent maintenance dialysis, age, waist circumference and albumin could be predictive factors of low skeletal muscle mass. Dialysis patients with such factors are recommended to evaluate nutritional status and physical performance to identify sarcopenia earlier and prevent progressive course of sarcopenia and frailty.